The Effect Of Fermenting Papaya Leaf Flour As A Feed Addition To Broiler Chicken Performance - P. Nababan; Yunilas; N. Br. Kataren; U. Hasanah; I. Siburian (Talenta Publisher, 2022)
Papaya leaves are one of the wastes that are commonly used as feed additives because they have good quality and are commonly used as medicine in livestock. This study aims to determine the effect of adding papaya leaf flour as a feed additive on the performance of broiler chickens. The study was conducted experimentally using a completely randomized design (CRD) with five treatments with five replications, namely P1 = ration without the addition of fermented papaya leaf flour, P2 = ration with the addition of 3% fermented papaya leaf flour, P3 = ration with the addition of 6% papaya leaf flour. Fermentation, P4 = ration with the addition of 9% fermented papaya leaf flour, P5 = ration with the addition of 12% fermented papaya leaf flour. The research parameters were feed consumption, body weight gain, and feed conversion. The results showed that the use of fermented papaya leaf flour up to 12% had a significant effect (P < 0.05) on consumption, body weight gain, and conversion. The study's conclusion showed that adding fermented papaya leaf flour as a feed additive of 12% was more efficiently used to improve broiler performance.